Alpha-glucosidase inhibitor and aroma from the flesh of Salak(Salacca zalacca) fruit, their metabolic demarcation and antidiabetic potential - Mat So'ad, Siti Zaiton; Siddiqui, Mohammad Jamshed Ahmad; Kasmuri, Abdul Razak; Rahman, Md. Mokhlesur (2018)
Salacca zalacca (Gaertn.) Voss (salak fruit or snake fruit) is a species of palm tree native to Southwest Java and North Sumatra in Indonesia. S. zalacca fruit is used indigenously as food and for medicinal applications in Southeast Asia. Due to its pleasant aroma, S. zalacca has potential in perfumery and pharmaceutical industries. In this study, the volatile aromas of S. zalacca fruits were extracted by conventional extraction methods such as steam distillation and solvent extraction methods. Nonconventional extraction technique being used was supercritical carbon dioxide extraction method (SC-CO2). We found that SC-CO2 is the most suitable technique to extract the volatile aroma from S. zalacca fruits. It is considered as a green extraction technique because it is renewable, produces little to no toxic wastes and has short extraction time. Steam distillation was not a suitable extraction method for S.zalacca as it produced inorganic compound. The percentage yields of SC-CO2 samples were higher (10 MPa, 30 oC: 0.2704 %; 25 MPa, 50 oC: 0.3634 %; 40 MPa, 70 oC: 0.2635 %) than the hexane (0.0511 %) and dichloromethane (0.1358 %) extractions but lower than the diethyl ether (0.5692 % ) solvent extraction. Evaluation of α-glucosidase inhibitory activity of S. zalacca fruit extracts were performed by conducted the study in correlation with Fourier transform infrared spectroscopy(FT-IR) fingerprint and utilized orthogonal partial least- square(OPLS). A total of 36 extracts were prepared by using different ethanol:water ratios (100, 80,60, 40, 20, 0%(v/v)). All extracts were evaluated for in vitro α-glucosidase inhibitory, measured by their IC50 values in comparison to that of quercetin. The result indicated as the ratio of water increased in the solvent, the α-glucosidase inhibitory activity decreased significantly. 60% ethanolwater extract exhibited the highest inhibition (IC50 15.94 ± 2.52 μg/mL), followed by 100% ethanol (IC50 19.15 ± 1.82 μg/mL). The extracts were not significantly different from the positive control (quercetin) (p < 0.05). A calibration model was applied to develop a rapid analytical method tool for quality control of this fruit. The OPLS biplot model identified several functional groups which actively induced αglucosidase inhibitory activity which were amines, fatty acids, esters, and sulfurcontaining compounds. The compound could be chlorogenic acid, caffeic acid, levodopa, ascorbic acid, and gallic acid. Subsequently, GC-MS were used to identify metabolites that may possess as α-glucosidase inhibitor. All metabolites was compared with the previously reported metabolites with significant α-glucosidase inhibitory activity which were citric acid, palmitic acid, stearic acid, oleic acid, 9- octadecanoic acid, gallic acid, stigmasterol and β-sitosterol. Overall study already explored the key potential of S. zalacca fruit as α-glucosidase inhibitor and may contributed as one of potential sources to develop an anti-diabetic agent in future.